On Writing with Photography - Weissberg, Liliane; Beckman, Karen Redrobe, 1971- (Book collections on Project MUSE., 2013)
This book explores what happens to texts - and images - when they are brought together, addressing a wide range of genres and media, including graphic novels, children's books, photo-essays, films, diaries, newspapers, and art installations. Together, these essays help explain how writers and photographers - past and present - have served as powerful creative resources for each other. -- Provided by publisher.